"Gnoseological Concupiscence" and the Lines of Division in Post-Conciliar Theology - Rowland, Tracey (Teologia w Polsce, 2020)
This article is a summary of the arguments contained in the author’s book Catholic Theology. It highlights the fault-lines between four of the most significant approaches to theology in the Post-Conciliar era. The author classifies these four approaches as: (1) Thomist theology, (2) Communio-style theology, (3) Concilium-style theology and (4) liberation theology.